Perceived urban environment attributes and obesity indices in adults: an 8-Nation study from Latin America - Moraes Ferrari, Gerson Luis (2022)
This study examines the associations between perceived urban environment attributes and obesity indices by country using data from an eight-nation study from Latin America. The data were collected from 8185 adults. The Neighbourhood Environment Walkability-abbreviated scale was used to assess perceived urban environment attributes. Obesity indices considered were body mass index, waist circumference, neck circumference, a body shape index and waist-to-height ratio. The perception of a more and better land use mix-diversity (β − 0.44; 95% CI − 0.59, − 0.28), traffic safety (− 0.39; − 0.66, − 0.12), and safety from crime (− 0.36; − 0.57, − 0.15) was associated with lower body mass index across the entire sample. Land use mix-diversity (− 1.21; − 1.60, − 0.82), street connectivity (− 0.26; − 0.37, − 0.15), and traffic safety (− 0.79; − 1.47, − 0.12) were negatively associated with waist circumference. Land use mix-diversity (− 0.11; − 0.20, − 0.03), land use mix-access (− 0.23; − 0.34, 0.12), walking/cycling facilities (− 0.22; − 0.37, − 0.08), and safety from crime (− 0.27; − 0.42, − 0.12) were negatively associated with neck circumference. No associations between perceived urban environment attributes and a body shape index were found. Land use mix-diversity (− 0.01; − 0.02, − 0.01), aesthetics (− 0.02; − 0.03, − 0.01), and safety from crime (− 0.02; − 0.04, − 0.01) were associated with waist-to-height ratio. Environmental interventions involving urban environment attributes are associated with obesity indices and, therefore, may help decrease the prevalence of overweight and obesity.